2017
DOI: 10.1111/1462-2920.13677
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis

Abstract: Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram-negative bacterial that live as a single individual capable of producing magnetic nano-particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Here, we used HPF/FS, for the first time, in combination with TEM and fluorescence confocal microscopy to study the ultrastructure of MMPs. As previously reported (Leao et al, 2017) but with more detail, we observed the conspicuous periphery-core architecture ( Fig. 3A, B, C, E and G), an axisymmetrical arrangement of cells along the eMMP longitudinal axis (Fig.…”
Section: Cellular Arrangement Within Ellipsoidal Mmpssupporting
confidence: 88%
See 2 more Smart Citations
“…Here, we used HPF/FS, for the first time, in combination with TEM and fluorescence confocal microscopy to study the ultrastructure of MMPs. As previously reported (Leao et al, 2017) but with more detail, we observed the conspicuous periphery-core architecture ( Fig. 3A, B, C, E and G), an axisymmetrical arrangement of cells along the eMMP longitudinal axis (Fig.…”
Section: Cellular Arrangement Within Ellipsoidal Mmpssupporting
confidence: 88%
“…B). Interestingly, the genes involved in magnetosome biosynthesis are well conserved among uni‐ and multicellular MTB from the Deltaproteobacteria class (Leao et al ., ). This result cannot distinguish between acquisitions by non‐magnetic multicellular microbes of magnetosome coding genes via horizontal gene transfer from evolution of MMPs from unicellular magnetotactic Deltaproteobacteria .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cytoplasmic pH in MTB collected from the acidic sediment was close to neutral in all MTB morphotypes (except for the intracellular granules produced by some MTB) as evidenced by the intracellular pH assay, these organisms likely have an efficient mechanism of maintaining the intracellular pH close to neutrality as do known acidophiles (Dopson et al, 2017). Lipid, sulfur and phosphorus-rich granules are commonly described in MTB (Lefèvre et al, 2010;Lefèvre et al, 2012;Leão et al, 2017). All these granules can have an acidic pH depending on the storaged compound(s) chemical form.…”
Section: Discussionmentioning
confidence: 99%
“…Several MMP species have been described at the level of 'Candidatus', most of them showing spherical shapes, and a few exhibiting ellipsoidal morphologies. Despite morphological differences, they show coherent phylogeny, structure, life cycle and behaviour (Keim et al, 2004a;Abreu et al, 2007;Zhou et al, 2012;Chen et al, 2015;Kolinko et al, 2014;Zhang et al, 2014;Chen et al, 2016;Leão et al, 2017). MMPs are motile only when forming the multicellular ensemble, whereas detached cells are immotile and probably dead .…”
Section: Introductionmentioning
confidence: 99%